An experimental study of electrochemical incompatibility between repaired patch concrete and existing old concrete. (20th June 2018) - Ali, M. Shafqat; Leyne, Eileen; Saifuzzaman, Mohammad; Mirza, M. Saeed
Highlights: Electrochemical incompatibility exists between repaired concrete and old concrete. Performance of the patch repair strategies for concrete bridge deck slabs is examined. Increased corrosion at the periphery of the repair and progressed into the repaired zone. Different measures are proposed to increase the service life of the repair system. Abstract: This research program examines the performance of different patch repair strategies for repairing concrete bridge deck slabs, damaged due to premature corrosion of embedded reinforcing steel bars (rebars). The electrochemical compatibility between the repaired patch concrete and the existing old concrete in fifteen (1000 mm × 1000 mm × 200 mm) specimens was examined using half-cell potential, chloride content, rebar mass loss and corrosion penetration rate tests. The experimental results showed that the potential difference between the repaired patch concrete and the existing old concrete local corrosion increased significantly at the periphery of the patch, and gradually progressed into the repaired zone. This effect varied from one repair technique to another. Different measures to increase the service life of the repair system are also proposed, such as incorporating a sacrificial embedded anode, an impressed current cathodic protection system, along with the use of surface coating or membrane as an additional line of defence.